Kehidupan Doa untuk Mencapai Kemurnian Batin Berdasarkan Pemikiran Bapa-Bapa Suriah - Margareta Ruy; Hendi (Voice, 2024)
This research explores the importance of prayer in human life as a path to inner purity and a closer relationship with God. By aiming the prayer as an important life practice to open the path of reconciliation between man and God, the researcher uses a literature research method that examined the writings of the Syrian Fathers as a reference. The author synthesizes the book "The Syriac Fathers on Prayer and Spiritual Life" by Sebastian Brock as a theoretical foundation in discussing prayer life. In this article, the author elaborates on the thoughts of the Syrian Fathers to deepen the understanding of prayer life. A pleasing prayer life is one that unites thoughts, feelings, and desires to be directed towards Christ. To reach this level, there needs to be a deep and silent experience of prayer, where all aspects of human existence: body, soul and spirit can be united. Through this process, man can experience deep repentance, where a broken and tearful heart can be renewed and purified by the divine presence.